Empathy training via Kalamazoo Consensus in remote and in-person medical communication: A randomized controlled trial - Giovan Battista Previti; Carlo Mazzatenta; Tommaso Bellandi; Francesco Niccolai; Dario Nieri; Valentina Ungaretti; Irene Cavasini; Alessandra Mazzoni; Stefano Maiorano; Luca Di Paolo; Veronica D'Elia; Monica Torre; et al. (PEC Innovation)
Background: Empathy is crucial in healthcare, facilitating effective communication and improving patient outcomes. Objective: This study aimed to evaluate the impact of tele-conference training based on the Kalamazoo Consensus Statement (KCS) on the empathy scores of newly hired physicians in a tele-visit simulation course. Methods: From September 2021 to April 2022, we conducted a randomized controlled trial involving 129 medical doctors from 13 hospitals in north-western Tuscany, with an age range of 31 to 42 years. Partecipants were randomly assigned to a trained group (TG) or a control group (CG). Both groups completed the Toronto Empathy Questionnaire (TEQ) and the Balanced Emotional Empathy Scale (BEES) before (T0) and after (T1) the training. The TG underwent a 12-h online communication training course. The CG only completed the questionnaires without further intervention. Results: Total sample included 129 partecipants. Results indicated a significant increase in TEQ scores for the TG (55,8 % of total sample; T0: 65.32; T1: 66.42, p = 0.032) and BEES scores (T0: 122.39; T1: 127.50, p = 0.000). The CG (44,2 %) experienced a decrease in TEQ scores (T0: 65.58; T1: 63.75, p = 0.000) but stable BEES scores (T0: 122.16; T1: 120.67, p = 0.317). Female participants consistently exhibited higher empathy scores than males, with training significantly enhancing scores for both genders. Conclusions: The tele-conference training effectively improved empathy scores among newly hired physicians. We recommend the implementation of KCS-based training to enhance empathy and communication skills in medical practice. Innovation: The pandemic has accelerated the use of tele-education and telemedicine, though opinions on their effectiveness remain divided. However, studies show that empathy can be enhanced through interactive online training, which offers significant innovations for both healthcare professionals' learning and patient care.